Geological peculiarities from the Konin Lignite Mine, central Poland: An overview - Wachocki, Robert; Chomiak, Lilianna; Klęsk, Jakub; Maciaszek, Piotr; Urbański, Paweł; Widera, Marek; Zieliński, Tomasz (Geologos, 2025)
The 80th anniversary (1945–2025) of the Konin Lignite Mine (KLM) invites some summaries of the mine’s characteristics. Therefore, the current study is devoted to rocks/sediments and tectonic or sedimentary structures that were observed and examined in lignite opencasts in the vicinity of the town of Konin. Some of them can be considered wonders and/ or curiosities of nature, some are unique, and others are quite common. Hence, they were generally defined as geological peculiarities in this article. In stratigraphic order they are sandstones, cleats, crevasse splays, palaeochannels and palaeosols. They represent various lithostratigraphic units (formations and members) of the Neogene of central Poland, while their age ranges from the Early Miocene to the earliest Pliocene. Among the listed objects, quartzite sandstones (situated below and between the lignite beds) and palaeosols in the Poznań Clays are very common, known from other lignite opencasts in Poland. In the case of cleats and crevasse splays occurring within the lignite seam exploited by the KLM, they are among the most numerous and best developed of all lignite-bearing formations in the world. On the other hand, the presence of palaeochannels in fine-grained sediments, constituting the overburden of the exploited lignite seam, provides additional and convincing evidence for the fluvial origin of the Poznań Clays.